Types of Tellurium Mineralization of Gold Deposits of the Aldan Shield (Southern Yakutia, Russia) - Larisa A. Kondratieva; Galina S. Anisimova; Veronika N. Kardashevskaia (Minerals, 2021)
The published and original data on the tellurium mineralization of gold ore deposits of the Aldan Shield are systematized and generalized. The gold content is related to hydrothermal-metasomatic processes caused by Mesozoic igneous activity of the region. The formation of tellurides occurred at the very late stages of the generation of gold mineralization of all existing types of metasomatic formations. 29 tellurium minerals, including 16 tellurides, 5 sulfotellurides and 8 tellurates have been identified. Tellurium minerals of two systems predominate: Au-Bi-Te and Au-Ag-Te. Gold is not only in an invisible state in sulfides and in the form of native gold of different fineness, but also is part of a variety of compounds: montbrayite, calaverite, sylvanite, krennerite and petzite. In the gold deposits of the Aldan Shield, three mineral types are distinguished: Au-Ag-Te, Au-Bi-Te, and also a mixed one, which combines the mineralization of both systems. The decrease in the fineness of native gold is consistent with the sequence and temperatures of the formation of Te minerals and associated mineral paragenesis from the epithermal–mesothermal Au-Bi-Te to epithermal Au-Ag-Te. The conducted studies allowed us to determine a wide variety of mineral species and significantly expand the area of distribution of Au-Te mineralization that indicates its large-scale regional occurrence in the Aldan Shield.